Hudson Bay Sea-Floor Photographs - Barber, F.; Grainger, E.; Pelletier, B. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1979)
A variety of bottom dwellers and some aspects of their interaction with habitat, as in lebensspuren, and with other animals are seen in photographs of the floor of Hudson Bay. The influence of ice-rafting on sediment type and distribution is depicted.